Pengaruh Perubahan Dimensi Kolom pada Perhitungan Struktur Tahan Gempa Gedung Beton Bertulang - Ripan Maulidan; Eko Walujodjati (Institut Teknologi Garut, 2025)
Columns are one of the structural elements that play a crucial role in supporting the strength of a building, and therefore require careful calculation when determining their dimensions. In the structural planning of the Cisaga Community Health Center (Puskesmas), there were several changes in the column dimensions to be used. The objective of this study is to understand the impact of these dimension changes on the seismic force calculations and reinforcement design of structural elements, particularly columns. The structural modeling was carried out through three-dimensional simulation using the ETABS V19 structural analysis program. Calculations were based on SNI 1726-2019 and SNI 2847-2019 standards. Based on the analysis, the building with 450 x 450 mm columns experienced a maximum seismic force that differed by 27% compared to the building with 300 x 300 mm columns. The maximum displacement occurred on the second floor, where the 300 x 300 mm column configuration resulted in 69% greater displacement in the x-direction and 71% in the y-direction. The reinforcement calculation for the 450 x 450 mm column yielded a main reinforcement ratio of 1.68%, whereas the 300 x 300 mm column required 5.04%. The 450 x 450 mm column also produced a greater stirrup spacing in the plastic hinge region compared to the 300 x 300 mm column. Larger column dimensions result in greater shear and seismic forces acting on the structure. The larger the column dimensions used, the greater the building’s stiffness against seismic loads.